Shell Companies - White Collars Mafia - Nitu, Alin Sergiu; Constantin, Aurelian (Acta Universitatis Danubius. Œconomica, 2022)
Money laundering is a topical issue, as it concerns both society as a whole, in terms of the public interest, and the individual, in terms of private interest. Money laundering, according to various established definitions, is a criminal way of making a profit from activities specific to the underground economy for which one wants to hide the forms and sources through which they take place. The forms, tools, ways and/ or techniques of money laundering know a variety of typologies, which adapt and modernize as they are discovered, analyzed and countered by the bodies and institutions empowered to eradicate them. One tool or means of money laundering, which can be said to be a prerogative of white-collar workers, is the use of "shell" companies, which are registered and operate legally, have no assets and no activity, only real financial assets. being an intermediary in the money-hiding circuit. These companies are professional organizations, acting in collusion with other commercial or non-commercial entities, banking or non-banking, financial or non-financial, the list being long and varied, intermediaries that also have apparent legality, usually internationally, in countries with jurisdictions. which can hardly be combated.